LANGUAGE ATTITUDES AND IDENTITY CONSTRUCTION OF TRILINGUAL LEARNERS IN A RURAL SCHOOL IN THE PHILIPPINES - Esteron, Jerico Juan (LLT Journal: A Journal on Language and Language Teaching, 2020)
Since its implementation in 2012, the Philippines? mother tongue-based multilingual education (MTB-MLE) program has already generated issues that point to the seemingly inadequate preparation of the education bureau when it comes to teacher training and instructional materials production. However, one concern that is seldom mentioned in the literature is the learners? attitude toward the languages they learn in the process. This is crucial because this attitude could reveal their learning motivations and formation of linguistic and sociocultural identity. Informed by the notion of language attitudes and construction of identity, this study explores the perception of trilingual children on their mother tongue and second languages?Ilocano, Filipino, and English, vis-à-vis their identity construction. Results show that most of the learners hold a positive attitude toward the three languages. However, the identified negative attitudes of some learners as regards these languages may cause pedagogical concerns linking to language teaching and the discourse of culture, nationalism, and globalization.DOI: doi.org/10.24071/llt.2020.230107